Research Status and Trend of M50 Bearing Steel Surface Strengthening Technology - ZHANG Hao, PAN Yongzhi, YANG Yanzhao, ZHUANG Qikai, LIANG Hao, MEN Xiuhua (Cailiao Baohu)
Bearings，regarded as the “heart” of aircraft engines，operate under extreme conditions involving high temperatures，high pressures，and high speeds，with fatigue being their primary failure mode.To enhance the performance of aerospace bearings and consequently improve the reliability and service life of aircraft engines，the application of surface strengthening technologies proves particularly crucial.Firstly，the primary failure modes of rolling contact fatigue in aerospace M50 bearing steel were reviewed based on the mechanisms of bearing failure，with subsurface-initiated rolling contact fatigue identified as the primary failure mode，and the causes of fatigue failure were subsequently discussed.Secondly，based on the severe plastic deformation mechanism，the strengthening modification effect of surface strengthening processes on the surface service performance of bearing steel was analyzed from the perspectives of grain deformation and stress strengthening.Through grain refinement and the introduction of residual compressive stress，the fatigue resistance of the material was significantly improved.Additionally，recent research progress on existing surface strengthening processes was summarized，including various methods such as ultrasonic rolling，shot peening and laser shock hardening.Finally，limitations of existing single-process approaches were identified，along with development directions for strengthening and modification processes specifically for M50 bearing steel.